Developing High School Students’ Reading Comprehension Skill of Narrative Texts through Question-Answer Relationship (QAR)-Based Small Group Discussions - Delia Sulistyoningrum; Mobit Mobit (FKIP - Universitas Riau, 2026)
The study investigates how the Question-Answer Relationship (QAR) strategy could be used to facilitate the development of students’ critical reading skills in the context of narrative texts and explores students’ responses to its implementation in small group discussions. The research was motivated by the need for more structured and student-centered strategies to enhance reading comprehension in senior high school settings. Employing a qualitative Classroom Action Research (CAR) design, the study was conducted in an 11th-grade class at a private senior high school in Karawang, Indonesia. Data were gathered through classroom observations and Focus Group Discussions (FGDs), then analyzed by using thematic analysis. The findings show that the teacher played a pivotal role in introducing QAR categories and guiding students in applying them through collaborative learning. The students demonstrated increased confidence, deeper comprehension, and greater motivation to engage with texts critically. The study concludes that QAR is an effective strategy to promote critical reading skills, support active student participation, and foster reflective classroom discussions. These results suggest that integrating structured questioning strategies such as the QAR into reading instruction can enhance both cognitive and affective dimensions of learning, especially when supported by consistent teacher facilitation and peer collaboration.